PENGARUH MODUL AJAR BERBASIS UNDERSTANDING BY DESIGN TERHADAP KEAKTIFAN SISWA DI SANGGAR BELAJAR KEPONG MALAYSIA - Tambunan, M. Ikhwan; Ismail Saleh Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to assess the impact of the Understanding by Design (UbD) instructional model on student participation at Sanggar Belajar Kepong, Malaysia. A quantitative method with a pretest-posttest single group design was used. The entire student body at Sanggar Belajar Kepong, totaling 15 students, served as the population, and purposive sampling was employed to select participants. The data collection tool was a 15-item multiple-choice test intended to evaluate student engagement in learning Indonesian, with a focus on folk tale content. Data analysis included tests for validity, reliability, normality, homogeneity, and hypothesis testing. Findings reveal a statistically significant increase in student engagement after the implementation of the UbD model, with a p-value below 0.05. The results affirm that the UbD approach effectively enhances student activity in five key areas: interaction with teachers, participation in discussions, active team involvement, confidence in answering questions, and effort in completing assignments. Overall, this study confirms that integrating the UbD model can serve as a practical method for boosting student participation in the learning process.